Glutathione affects the transport activity of Rhizobium leguminosarum 3841 and is essential for efficient nodulation. Issue 8 (23rd February 2017) - Cheng, Guojun; Karunakaran, Ramakrishnan; East, Alison K.; Munoz-Azcarate, Olaya; Poole, Philip S.
Abstract: As glutathione (GSH) plays an essential role in growth and symbiotic capacity of rhizobia, a glutathione synthetase ( gshB ) mutant of Rhizobium leguminosarum biovar viciae 3841 (Rlv3841) was characterised. It fails to efficiently utilise various compounds as a sole carbon source, including glucose, succinate, glutamine and histidine, and shows 60%–69% reduction in uptake rates of glucose, succinate and the non-metabolisable substrate α-amino isobutyric acid. The defect in glucose uptake can be overcome by addition of exogenous GSH, indicating GSH, but not its bacterial synthesis, is required for efficient transport. GSH is not involved in the regulation of the activity of Rlv3841's transporters via the global regulator of transport, Pts NTR . Although lack of GSH reduces transcription of the branched amino acid transporter, this was not the case for all uptake transport systems, for example, the amino acid permease. This suggests GSH alters activity and/or assembly of transport systems by an unknown mechanism. In interaction with plants, the gshB mutant is not only severely impaired in rhizosphere colonisation, but also shows a 50% reduction in dry weight of plants and nitrogen-fixation ability. This reveals that changes in GSH metabolism affect the bacterial–plant interactions required for symbiosis. Abstract : Glutathione is needed for bacteria to fix nitrogen efficiently in symbiosis with legumes.